Ultrasonication of in vitro potato single node explants Activation and recovery of antioxidant defence system and growth responses - Dobránszki, Judit (Plant physiology and biochemistry : PPB, 2017)
Copyright © 2017 Elsevier Masson SAS. All rights reserved.